Lacosamide and Levetiracetam Have No Effect on Sharp-Wave Ripple Rate - Kudlacek, Jan; Chvojka, Jan; Posusta, Antonin; Kovacova, Lubica; Hong, Seung Bong; Weiss, Shennan; Volna, Kamila; Marusic, Petr; Otahal, Jakub; Jiruska, Premysl (Frontiers in Neurology, 2017)
Pathological high-frequency oscillations (pHFOs) are a novel marker used to improve the delineation of epileptogenic tissue and hence, the outcome of epilepsy surgery. Their practical clinical utilization is curtailed by the inability to discriminate them from physiological oscillations due to frequency overlap. Although it is well documented that pathological HFOs are suppressed by antiepileptic drugs, the effect of antiepileptic drugs on normal HFOs is not well known. In this experimental study, we have explored whether physiological HFOs (sharp-wave ripples) of hippocampal origin respond to antiepileptic drug treatment. The results show that application of a single dose of levetiracetam or lacosamide does not reduce the rate of sharp-wave ripples. In addition, it seems that these new generation drugs do not negatively affect the cellular and network mechanisms involved in sharp-wave ripple generation, which may provide a plausible explanation for the absence of significant negative effects on cognitive functions of these drugs, particularly on memory.